Perancangan Media Pembelajaran IPA Kelas VII Menggunakan Genially Di MTs Swasta Terpadu Guguak Randah - Yulia Mutiara Insani; Hari Antoni Musril; Riri Okra; Sarwo Derta (Joined Journal (Journal of Informatics Education), 2024)
This research is based on problems that exist at MTs ST Guguak Randah, the teaching materials used by teachers are study guides and worksheets. The use of learning media is very rare, so students feel bored when studying. Based on these problems, the researchers provided a solution by creating learning media that was used in a friendly, attractive manner. The author offers a solution by utilizing technology, especially to create a learning media for class VII science subjects using Genially at MTs ST Guguak Randah that is valid, practical and effective. The research method used is the Research and Development (R&D) method. Meanwhile, the development model uses the Hannafin and Peck model, which consists of three stages, namely (1) needs analysis, (2) design, (3) development and implementation, where each step includes revision and evaluation. It can be concluded that this media product was designed based on research findings that have been carried out and are declared valid, practical and effective. This can be assessed from the results of the product testing that the author carried out, through validity testing the final result was 0.86 which was within the valid criteria, then with practicality testing the final result was 0.89 which was very practical criteria and effectiveness testing obtained a final result of 0.80 with high criteria.